(3eMGSHI GdTQcGJ (B/s - (3cQGLI, YHO GdMedje eMehOs ((3YeGf(B: s (3OGQ GdCed(B, s, 2000)
(3eONd Gdi eMGSHI GdTQcGJ(B- (3TQcI GdJVGef GdYGOjI(B- (3GdMSGHGJ GdeJYdbI HGdTQcGA(B- (3GdJYOjd aj QCS GdeGd(B- (3GdLQO hGdMSGHGJ GdNJGejI hGdejRGfjI GdYehejI(B- (3aSN GdTQcI GdYGOjI hJUajJgG (B- (3GdTQcGJ GdeSGgeI(B- (3GdMSGHGJ GdNJGejI hGdejRGfjI GdYehejI(B- (3GdEMJjGWGJ, GdeNUUGJ(B- (3GdJUajIaj GdTQcGJ GdeSGgeIs
Keywords: (3GdTQcGJs; (3GdeMGSHIs